Skutki prawnofinansowe wyroku Trybunału Konstytucyjnego K13/11 dla województwa mazowieckiego - Bogucka-Felczak, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
On 4 March, 2014 the Constitutional Tribunal adjudicated that Art. 31 and Art. 25 of the Act of 13 November, 2003 on revenues of local self-governments OJ of 2010 No. 80, item 526 and No. 127, item 857, and of 2011 No. 139, item 814, No. 207, item 1230 and No. 234, item 1385, and of 2012 item 354 and of 2013 items 193 and 1609, wherever they did not guarantee regional governments the right to keep a material part of their own revenues for the purpose of fulfilling their own responsibilities, were in contravention of Art. 167 paragraphs 1 and 2 in conjunction with Art. 166 paragraph 1 of the Constitution of the Republic of Poland, and in contravention of Art. 9 paragraph 5 of the European Charter of Local Self-Government done at Strasbourg on 15 October, 1985 OJ of 1994, No. 124, item 607, and of 2006, No. 154, item 1107.The said regulations, found to be in contravention of the Constitution of the Republic of Poland, were to lose their legal validity 18 months after the judgement’s publication in the Official Journal of Laws of the Republic of Poland, unless the same had been earlier rescinded or amended by the legislator, which, according to the Tribunal, ensued from the level of complexity of the issues to which the said regulations pertained.Concurrently, in the reasons for the judgement, the Constitutional Tribunal stated that the said regulations “Within the said timeframe should be applied by all parties involved”.The objective of this study is to present the legal and financial situation of the Mazowieckie Province resulting from the Constitutional Tribunal’s judgement reference K 13/11 during the deferment of the derogation effect on the provisions within Art. 31 and Art. 25 of the act on revenues of local self-governments. This study presents the possible legal ways that might provide to the given local self-government an option of reducing its contributions to the regional component of the general subsidy whose terms of payment had expired either before the said judgement was announced, or during the derogation effect deferment period, and whose amounts had been determined in terms of the regulations found to be unconstitutional, as well as enable the law administration bodies to recognise such an option.
Keywords: odwołanie od wyroku; Trybunał Konstytucyjny; województwo mazowieckie